Exploring Motivational Factors in Pre-Service English Teachers’ Efforts to Improve Speaking Skills - Hutagalung, Magdalena; Sulistyani, Ummi Nur Laila (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the motivational factors influencing pre-service English teachers’ efforts to improve their speaking skills during the LANTIP teaching practicum at Universitas Negeri Semarang. Employing a qualitative descriptive design, data were collected from 30 pre-service English teachers through open-ended questionnaires and were triangulated with semi-structured interviews involving selected participants. The data were analyzed using thematic analysis. The findings reveal that speaking motivation during practicum emerged from an interaction between intrinsic and extrinsic factors. Intrinsically, participants were motivated by the desire to construct a credible professional identity and to regulate confidence in classroom interaction. Extrinsically, mentor feedback, student responses, and school language environments shaped participants’ motivation to improve speaking performance. Practicum experiences, including speaking difficulties and emotional challenges, functioned as catalysts for motivational adjustment rather than as barriers. Based on these findings, this study recommends that English teacher education programs provide supportive mentoring, structured opportunities for authentic English use, and guidance in managing speaking-related anxiety to sustain pre-service teachers’ speaking motivation during teaching practicum.